The relation of electrical conductivity profiles and modulus data using the example of STO:Fe single crystals: A path to improve the model of resistance degradation. (15th September 2016) - Bayer, Thorsten J.M.; Wang, Jian-Jun; Carter, Jared J.; Moballegh, Ali; Baker, Jonathon; Irving, Douglas L.; Dickey, Elizabeth C.; Chen, Long-Qing; Randall, Clive A.
Abstract: Resistance degradation in perovskites is characterized by an increase in current over time with applied electric field. This behavior can be simulated and spatially resolved conductivity profiles can be measured, but some inconsistencies remain. A new approach to address these problems is presented that utilizes time-resolved impedance spectroscopy with an applied DC voltage to provide new insight into the resistance degradation phenomenon. In particular, this method allows the in-situ acquisition of spatio-temporal variations in conductivity. In SrTiO3 a single bulk-dominated maximum of the imaginary part of the modulus M″ transitions to two maxima during degradation, reflecting the hole conductivity in the anode region and the electron conductivity in the cathode region. To clarify the influence of conductivity profiles on impedance data, the reversed route is presented by using simulated conductivity profiles to calculate impedance data. It will be emphasized that this methodology is not limited to the perovskite system considered here, but can be adapted to any kind of system characterized by a spatially varying conductivity. Graphical abstract: